K(+)-Selective Inward-Rectifying Channels and Apoplastic pH in Barley Roots - Amtmann, Anna (American Society of Plant Physiologists, 1999)
Recent structure-function analysis of heterologously expressed K(+)-selective inward-rectifying channels (KIRCs) from plants has revealed that external protons can have opposite effects on different members of the same gene family. An important question is how the diverse response of KIRCs to apoplastic pH is reflected at the tissue level. Activation of KIRCs by acid external pH is well documented for guard cells, but no other tissue has yet been studied. In this paper we present, for the first time to our knowledge, in planta characterization of the effects of apoplastic pH on KIRCs in roots. Patch-clamp experiments on protoplasts derived from barley (Hordeum vulgare) roots showed that a decrease in external pH shifted the half-activation potential to more positive voltages and increased the limit conductance. The resulting enhancement of the KIRC current, together with the characteristic voltage dependence, strongly relates the KIRC of barley root cells to AKT1-type as opposed to AKT3-type channels. Measurements of cell wall pH in barley roots with fluorescent dye revealed a bulk apoplastic pH close to the pK values of KIRC activation and significant acidification of the apoplast after the addition of fusicoccin. These results indicate that channel-mediated K(+) uptake may be linked to development, growth, and stress responses of root cells via the activity of H(+)-translocating systems.